Particle energization in space plasmas: towards a multi-point, multi-scale plasma observatory - Retino Alessandro; Khotyaintsev Yuri; Le Contel Olivier; Marcucci Maria Federica; Plaschke Ferdinand; Vaivads Andris; Angelopoulos Vassilis; Blasi Pasquale; Burch Jim; De Keyser Johan; Dunlop Malcolm; Dai Lei; et al. (SPRINGER, 2022)
This White Paper outlines the importance of addressing the fundamental science theme "How are charged particles energized in space plasmas" through a future ESA mission. The White Paper presents five compelling science questions related to particle energization by shocks, reconnection, waves and turbulence, jets and their combinations. Answering these questions requires resolving scale coupling, nonlinearity, and nonstationarity, which cannot be done with existing multi-point observations. In situ measurements from a multi-point, multi-scale L-class Plasma Observatory consisting of at least seven spacecraft covering fluid, ion, and electron scales are needed. The Plasma Observatory will enable a paradigm shift in our comprehension of particle energization and space plasma physics in general, with a very important impact on solar and astrophysical plasmas. It will be the next logical step following Cluster, THEMIS, and MMS for the very large and active European space plasmas community. Being one of the cornerstone missions of the future ESA Voyage 2050 science programme, it would further strengthen the European scientific and technical leadership in this important field.